Relationship between Affective Commitment and Work Engagement in Employees of Savings and Loans Cooperatives in Kupang City - Tirza Risma Koroh; M. K. P. Abdi Keraf; Yeni Damayanti (Universitas Nusa Cendana, 2021)
Micro, Small, and Medium Enterprises (MSME) and cooperatives in NTT, especially in the city of Kupang, have a strategic role in the economic development of the community, especially in overcoming poverty. This makes organizations pay important attention to Organizational Commitment, especially the affective commitment that employees have so that services can be carried out properly. This study aims to determine the relationship between affective commitment and work engagement among cooperative employees in Kupang City. The type of research used is quantitative research with correlational methods. Sampling using purposive sampling technique with a total sample of 81 employees who work in cooperatives in Kupang City. Data collection used is a modification of the affective commitment scale developed by Meyer, Allen & Smith (1993) and an adaptation of the work engagement scale developed by Schaufeli & Bakker (2004). The analysis technique uses Pearson Product Moment Correlation and shows that there is a significant relationship between affective commitment and work engagement where the Pearson Correlation value= 0.225 with a significance of 0.044. This shows that employees who work in cooperatives in Kupang City have high work engagement and affect the level of affective commitment shown in the cooperative where they work.